Membraneless flow battery leveraging flow-through heterogeneous porous media for improved power density and reduced crossover. Issue 102 (21st October 2016) - Suss, M. E.; Conforti, K.; Gilson, L.; Buie, C. R.; Bazant, M. Z.
Abstract : A novel membraneless flow battery architecture, which leverages flow-through heterogeneous porous media, yields improved power density and reduced crossover. Abstract : We propose and demonstrate a novel flow battery architecture that replaces traditional ion-exchange membranes with less expensive heterogeneous flow-through porous media. Compared to previous membraneless systems, our prototype exhibits significantly improved power density (0.925 W cm −2 ), maximum current density (3 A cm −2 ), and reactant crossover, shown by the proposed experimentally-validated crossover model.